2013
DOI: 10.1093/nar/gkt100
|View full text |Cite
|
Sign up to set email alerts
|

Coactivators enable glucocorticoid receptor recruitment to fine-tune estrogen receptor transcriptional responses

Abstract: Nuclear receptors (NRs) are central regulators of pathophysiological processes; however, how their responses intertwine is still not fully understood. The aim of this study was to determine whether and how steroid NRs can influence each other’s activity under co-agonist treatment. We used a unique system consisting of a multicopy integration of an estrogen receptor responsive unit that allows direct visualization and quantification of estrogen receptor alpha (ERα) DNA binding, co-regulator recruitment and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 51 publications
(44 reference statements)
4
55
0
Order By: Relevance
“…Despite there being only nine breast cancer cases in the sample, we observed a negative association with G activity (the average G activity was lower among the women who developed breast cancer compared with those who did not). This is consistent with the observation that GR stimulation decreases the risk of relapse in breast tumors that are ER positive (54) due to cross talk between ER and GR (54,55). We also observed an association between G activity and alcohol intake as reported during the first interview (which for some of the individuals was 4 years before the time of blood draw).…”
Section: Discussionsupporting
confidence: 91%
“…Despite there being only nine breast cancer cases in the sample, we observed a negative association with G activity (the average G activity was lower among the women who developed breast cancer compared with those who did not). This is consistent with the observation that GR stimulation decreases the risk of relapse in breast tumors that are ER positive (54) due to cross talk between ER and GR (54,55). We also observed an association between G activity and alcohol intake as reported during the first interview (which for some of the individuals was 4 years before the time of blood draw).…”
Section: Discussionsupporting
confidence: 91%
“…It is a well-known fact that the combinatorial expression of all the NRs is important in determining the prognosis and avenues for the treatment [21,22]. However, fewer studies have been carried out on the expression of all the steroid hormone receptors by examining the action of one hormone at a time, and mostly a reductionist approach was used [23]. Studies using GR with PR [24,25] or ERa with RAR [26,27] show both competitive and co-operative interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also demonstrated the antagonistic effect of estrogen by glucocorticoids in ER/GR-positive breast and uterine carcinoma cells. Using multiple estrogen-responsive transcriptional assay system, steroid receptor co-activators (SRC 2, SRC 3) with MED 14 (mediator component); it was found that GR recruits five-time ER transcriptional responses under multiple hormone stimuli using GFP-ERa, HeLa-PRL cells [23]. Dex counteracts the stimulatory effect of E2 on MCF-7 cells and inhibits cell proliferation, and the down-regulation of ER by GCs is by attenuation and not by negative response.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Briefly, for the transcription factor (TF) assay, HeLa cells stably expressing the green fluorescent protein (GFP)-tagged androgen receptor (AR) were plated into 384-well plates in the DMEM/F12 medium supplemented with 5% charcoal stripped fetal bovine serum (S-FBS). After 48 h, either dihydrotestosterone (DHT) or DMSO was added to wells to a final concentration (10 nM, 0.5%), and plates were incubated for an additional 24 h. For the nuclear spot (NS) assay, HeLa cells containing integrated prolactin promoter elements and stably expressing the GFP-tagged estrogen receptor (ER) were plated into 384-well plates in the phenol red-free DMEM supplemented with 5% charcoal stripped and dialyzed FBS.…”
Section: Sample Preparationmentioning
confidence: 99%
“…We have validated that these cells allow us to characterize physiological responses to hormones and their effect upon ER DNA binding, promoter/chromatin remodeling, coregulator recruitment, and mRNA production. 14,26,27 We have also used these cell lines to characterize how environmental estrogens differentially affect the ER response. 13 The image analysis tools to perform these studies have been incorporated into the mIA algorithm editor, creating the predefined ''Nuclear Spot'' analysis pipeline.…”
Section: 26mentioning
confidence: 99%